Severe bleeding from a duodenal ulcer after orthognathic surgery: a case report. Issue 6 (June 2020) - Pham, Matthew; Dunlop, Natalie; Pham, Linda; Turvey, Timothy
Abstract: Chronic non-steroidal anti-inflammatory drug use is strongly associated with peptic ulcer disease, and corticosteroid use has also been cited as a risk factor. Both are frequently prescribed for short courses after orthognathic surgery to minimize edema. It appears that no cases of severe bleeding from a duodenal ulcer have been reported during the postoperative period after orthognathic surgery. This case describes a patient who experienced this severe bleeding despite having no risk factors.